Comparison of the heart rate and blood lactate responses of different small sided games in young soccer players - Köklü, Y.; Alemdaroglu, U. (Sports, 2016)
The purpose of this study was to compare the percentage of maximum heart rate (%HRmax), blood lactate (La-), and rating of perceived exertion (RPE, CR-10) responses across different formats of small-sided games (SSG) in elite young soccer players. Fourteen players (average age 16.7 ± 0.6 years; height 177.6 ± 4.1 cm; body mass 66.3 ± 4.7 kg; average training age 6.7 ± 1.6 years; percentage of body fat 8.4 ± 2.6%) volunteered to perform the YoYo intermittent recovery test (level 1) and eight bouts of soccer drills including 2-a-side, 3-a-side, and 4-a-side games without goalkeepers in random order at two-day intervals. Heart rates were monitored throughout the SSGs, whereas the RPE and venous blood lactate were determined at the end of the last bout of each SSG. The differences in La-, %HRmax, and RPE either across the different SSGs or between the bouts were identified using 3 × 8 (games × exercise bouts) two-way analysis of variance with repeated measures. Significant differences were found in terms of La-, RPE, and %HRmax among the different types of SSG (p = 0.05). 3-a-side and 4-a-side games elicited significantly higher responses than 2-a-side games in terms of %HRmax (p = 0.05), whereas 4-a-side games resulted in significantly lower La- and RPE responses compared to 2-a-side and 3-a-side games. The results of this study show that physiological responses differ according to the numbers of players involved in small-sided games. Therefore, it can be concluded that 3-a-side and 4-a-side games could be more effective in improving high intensity aerobic performance than 2-a-side games, which in turn are more appropriate for developing anaerobic performance